Dielectric spectra of polythiophene nanoparticles synthesized at different magnetic flux densities - Serin, Merih; Yakut, Sahin; Ulutas, Kemal; Caliskan, Murat; Bozoglu, Deniz; Deger, Deniz; Huner, Keziban; Karaman, Ferdane (NATL INST OPTOELECTRONICS, 2022)
Polythiophene nanoparticles successfully synthesized at different magnetic flux densities, which have values between 1,5-4,6 kGauss, were studied. The samples were prepared by dropping the dilute colloidal solutions of the PTh nanoparticles in pure water on the copper grids coated with carbon film. The sizes of polythiophene nanoparticles were determined by STEM analysis. It was observed that polythiophene nanoparticles were aggregated by the effect of magnetic flux. Dielectric measurements were performed using an impedance analyzer in the frequency range 0.1Hz-20MHz at room temperature. Three polarization mechanisms were detected. The AC conductivity obeys the Jonscher Law. The results obtained for polythiophene without and with magnetic flux effect were compared. It was observed that the presence of magnetic flux affects the structure of polythiophene by increasing the electrical capacitance at frequencies lower than 10(2) Hz and frequencies higher than 10(5)Hz. However, among the samples under the influence of magnetic flux, there isn't a remarkable difference with increasing flux density.
Keywords: Polymer composite; Nanoparticles; Magnetic flux; Dielectric spectroscopy; AC conductivity; ELECTRICAL-CONDUCTIVITY; OXIDE); COMPOSITES; RELAXATION; Materials Science; Optics; Physics